Brace and core stabilization to decrease vertebral curve in scoliosis cases scoliometer parameter and taps: a case study - Andrew Wijaya Saputra; Ruth Golda Meir; Riza Pahlawi (Physical Therapy Journal of Indonesia, 2023)
Introduction: Scoliosis is a disorder characterized by lateral curvature and rotation of the spine. The initial phase begins with a triggering event during the growth period. Characteristics that can be seen in scoliosis patients are differences in posture on the right and left sides, the rotation of the spine, the presence of hump, and other complications, namely pain and tightness. Methods: This study was a case study with a brace method accompanied by CSE, which was carried out for approximately three months with an intensity of exercise 2 times a week and a home exercise program. The modified Borg scale measures shortness of breath. Pain is calculated using a visual analog scale. While scoliosis disorders are measured using two tools, namely the scoliometer and the Trunk Appearance Perception Scale (TAPS). Results: Using objective parameters, namely the scoliometer. The degree of a scoliosis curve decreases in the thoracic part, with the initial value at 10° to 7°. Then there is no significant reduction in the lumbar region, with the initial interpretation at 6° and back to 6°. The result obtained through TAPS is also a stagnant number which is interpreted as no change in numbers too large or small, which means that the patient does not feel any significant changes in posture after going through an exercise program. Conclusions: It can be concluded that there was a change in the scoliosis curve of the thoracic part by giving a brace accompanied by core stability exercises. However, this technique was less effective in the lumbar area. Behind that, when viewed during activities, patients felt a decrease in the intensity of tightness and pain.